UPAYA MENINGKATKAN HASIL BELAJAR SISWA KOMPETENSI MINYAK BUMI DAN GAS ALAM MELALUI PENERAPAN PEMBELAJARAN COLLEGE BALL - Yusuf Yusuf (Jurnal Redox, 2018)
learning outcomes of class X.1 students at SMAN 1 Ciwaringin have not reached the standard of competence (KKM) set at school yet. The problem of chemistry learning is that the teacher in the learning process still uses conventional methods with teacher-centered lectures, not using student-centered learning models yet, so that students' thinking skills are less optimized to be more critical and more effective through application of college ball type active learning. This Classroom Action Research design consists of two cycles, each cycle consisting of four stages, namely planning, observing and reflecting. Research subjects are teachers and students of class X.1. Data collection techniques use observation and test results. The results of the study showed that before the study of chemistry learning outcomes, students obtained an average value of 68.10 with classical completeness of 37.43%. After conducting research in the first cycle obtained an average value of 78.20 with classical completeness of 83.40. In the second cycle the average value and completeness of classical learning has reached the indicator of minimum completeness success, namely the value of completeness learning ? 76 with classical completeness 83%. The conclusion of this study is the application of college ball type active learning can improve student activity, teacher performance and student learning outcomes in teaching and learning process. Keyword : Learning outcomes, collage ball learning, hasil belajar